INTRA-ARTICULAR SYNOVIAL HEMANGIOMA OF KNEE OVERLYING POSTERIOR CRUCIATE LIGAMENT - A CASE REPORT - S., Dileep K.; Kanakaraddi, Sandeep V.; S., Vidyasagar J.V.; S., Radha; Aroor, Akshatha Rao (Journal of Health and Allied Sciences NU, 2012)
Hemangioma of synovium is a rare benign tumor that can arise from any surface lined by synovium. Intra-articular synovial hemangioma is most common in the knee joint. The diagnosis is difficult as the signs and symptoms are nonspecific. We hereby report a hitherto unreported case of synovial hemangioma of knee overlying posterior cruciate ligament, its MRI findings and discuss the appropriate management
Keywords: posterior cruciate ligament; hemangioma; synovium; knee